The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4254/wjh.v9.i33.1253
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and therapeutic challenge of heart failure after liver transplant: Case series

Abstract: Heart failure (HF) following liver transplant (LT) surgery is a distinct clinical entity with high mortality. It is known to occur in absence of obvious risk factors. No preoperative workup including electrocardiogram, echocardiography at rest and on stress, reasonably prognosticates the risk. In patients of chronic liver disease, cirrhotic cardiomyopathy, alcoholic cardiomyopathy, and stress induced cardiomyopathy have each been implicated as a cause for HF after LT. However distinguishing one etiology from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…103 After LT, the prevalence of cardiomyopathy and heart failure, defined by a decrease in the LV ejection fraction, has been reported in the 3 to 7% range. 106,107 Management of heart failure after LT does not differ from its usual management. In general, CCM normalizes after LT, but results have been mixed.…”
Section: Cardiovascular Management and Hemodynamicsmentioning
confidence: 99%
“…103 After LT, the prevalence of cardiomyopathy and heart failure, defined by a decrease in the LV ejection fraction, has been reported in the 3 to 7% range. 106,107 Management of heart failure after LT does not differ from its usual management. In general, CCM normalizes after LT, but results have been mixed.…”
Section: Cardiovascular Management and Hemodynamicsmentioning
confidence: 99%
“…TS has most commonly been reported in elderly women with neurological or psychiatric disorders, but is increasingly being reported in postoperative patients [1,4]. Recently, several case series and retrospective studies have described TS in liver transplantation (LT) patients in the perioperative period [1,5]. In a retrospective, single-center study of 1752 liver transplants, the incidence of TS was found to be 1.4% [6].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment for TS depends on severity and patient response to therapies. Strategies specific to managing acute left ventricular dysfunction in LT patients are not well-defined, but in general, first-line treatments for low cardiac output are diuretics, inotropic therapy, and vasopressors [5,7,[19][20][21]. If there is decreased perfusion secondary to vasoconstriction, first-line treatment should include vasodilators [22].…”
mentioning
confidence: 99%
“…However, CCM often remains unrecognised when using traditional cardiovascular imaging modalities [15] and heart failure can be observed after LT even after all preoperative tests are negative [16]. Thus, newer more sensitive echocardiography indices as well as other imaging modalities, such as Cardiac Magnetic Resonance (CMR), are needed to improve the diagnostic approach of CCM, portopulmonary hypertension and other complications of end-stage-liver-disease.…”
Section: Introductionmentioning
confidence: 99%